Differentials of the immunization program in rural Bangladesh - Kamal, Firoz M.; Hadi, AbduUahel; Chowdhury, AMR (BRAC Research and Evaluation Division (RED), 2019)
This study investigated the association of immunization coverage with some selected socioeconomic variables in rural Bangladesh. It was conducted in 75 villages in I 0 areas of five administrative divisions. The eligible interviewees were the mothers having a child of age 12 to 23 months living in the ~elected villages. Both paternal and maternal education of 4-5 years of schooling were found to have a significant influence on immunization. No significant association exists between immunization coverage and child's sex. household land and labor sale. Parental religion impacts significantly. Exposure to media like radio increases predictability of immunization by about two folds. Most people favor none or minimal userfee, therefore restricting the self-sustainability of the program. An increase in parental education enhances affordability of userfees.